Era Baru Pendidikan Indonesia dalam Mengoptimalkan Peran Pedagogik dalam Implementasi Kurikulum Merdeka - Intan Aprilianti Pratiwi; Yusuf Tri Herlambang; Tatang Muhtar (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Education is the main aspect in developing a nation's civilization, education plays a role in developing economic, social and cultural aspects. The independent curriculum is designed to improve the quality of education through flexible learning and emphasizing competency development, the role of teachers and Pancasila values. This research aims to analyze the implementation of the independent curriculum as an effort to improve the quality of education in Indonesia in facing the challenges of the times. The research method used is the literature study method, through the collection and analysis of various literature sources such as journals, scientific articles, books, official reports and other relevant literature. The focus of the study emphasizes pedagogical approaches, the role of teachers, and the integration of values ​​in the independent curriculum. The research results show that the independent curriculum can overcome the limitations of the previous curriculum, by providing doctrine for teachers in designing learning that suits students' needs. Humanistic and constructivist approaches support learning that is meaningful and relevant to real life situations, while project-based and contextual learning can improve students' critical thinking skills, collaboration and independence. Implementation of this curriculum requires ongoing teacher training and community involvement. The independent curriculum has great potential in creating a generation that is not only skilled and knowledgeable, but also has strong character and is able to face the challenges of the times, namely globalization and digitalization.